2004
DOI: 10.1345/aph.1e012
|View full text |Cite
|
Sign up to set email alerts
|

Leflunomide-Associated Pancytopenia With or Without Methotrexate

Abstract: The risk of pancytopenia during leflunomide therapy appears to be increased when the drug is combined with methotrexate and in older patients. Onset may be delayed, and ongoing monitoring of blood counts is essential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
2

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(21 citation statements)
references
References 13 publications
1
18
0
2
Order By: Relevance
“…As female rats were more sensitive to MTX-induced anaemic changes than male rats, leukocytopenia was observed only in female rats. These changes were consistent with the data obtained from patients suffering from anaemia and pancytopenia and who were taking MTX during therapy (Chan et al, 2004;Cohen et al, 2005;McEwen et al, 2007). Interestingly, MTX caused an inverse effect on platelet, i.e.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…As female rats were more sensitive to MTX-induced anaemic changes than male rats, leukocytopenia was observed only in female rats. These changes were consistent with the data obtained from patients suffering from anaemia and pancytopenia and who were taking MTX during therapy (Chan et al, 2004;Cohen et al, 2005;McEwen et al, 2007). Interestingly, MTX caused an inverse effect on platelet, i.e.…”
Section: Discussionsupporting
confidence: 91%
“…Individual clinical data show that female patients are more likely to be affected than male patients (Chan et al, 2004;Lim et al, 2005), however those should be interpreted carefully as woman is generally liable to rheumatoid arthritis. Nevertheless, an earlier assessment would be important for therapeutic indications for which patient populations are at higher risk of pancytopenia, e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Methotrexate and leflunomide inhibit cell replication, and leukopenia can be a side effect of their administration (36,116,117). One of us has previously suggested that myelosuppression forms a part of the action of methotrexate as a DMARD (86).…”
Section: Cytokine Blockade Tnf Il-1 and Il-6mentioning
confidence: 99%
“…13,14 Chan et al suggested that the risk of myelotoxicity associated with lefl unomide was increased in older patients (median age, 65.5 years) and on administering a combination of lefl unomide and MTX. In the present case, although the patient was elderly, lefl unomide and MTX were not administered simultaneously.…”
Section: Discussionmentioning
confidence: 99%